Mastering Linux Shell scripting : a practical guide to Linux command-line, Bash scripting, and Shell programming /: a practical guide to Linux command-line, Bash scripting, and Shell programming. (2018) - Ebrahim, Mokhtar; Mallett, Andrew
No abstract available